Analysis Of Factors Influencing Consumer Purchasing Decisions In The Jakarta Metropolitan Area: A Study On Clothing Retail In Jabodetabek - Khairunnisa, Shafia Ashma; Hadiprawoto, Triana Rahajeng`` (Politeknik Siber Cerdika Internasional, 2024)
The research examines the impact of store design and atmosphere on consumer purchasing decisions in Greater Jakarta (Jakarta, Bogor, Depok, Tangerang, Bekasi). It analyzes the direct influence of store design and atmosphere and their mediating role with window display, mannequin display, visual merchandising, music, light and color, and signage. The study also evaluates the moderating effect of perceived service quality and assesses the direct impact of product, price, and promotion. Using a quantitative, descriptive approach, data were analyzed with Structural Equation Modeling (SEM) and model fit evaluation using SPSS 26 and SmartPLS 3.0. Results indicate that store design and atmosphere significantly impact purchasing decisions, with window display, mannequin display, visual merchandising, music, light and color, and signage mediating this impact. Perceived service quality moderates the relationship, while product, price, and promotion directly impact purchasing decisions. The study suggests that fashion retailers in metropolitan Jakarta should focus on store design, atmosphere, and service elements to enhance purchasing decisions and develop effective consumer strategies.